Cultural semiotic in Dayak's Babalai ceremonial at Paramasan as an form of maintaining Dayak language - Fajarika Ramadania; Johan Arifin (SOCIA: Jurnal Ilmu-Ilmu Sosial, 2019)
This research is entitled "Cultural Semiotic in Dayak’s Babalai ceremonial at Paramasan as a form of maintaining traditional language". This research has long-term goal of introducing Dayak Language in general and Dayak language culture, in particular, to attract tourists to visit Paramasan, Banjar District of South Kalimantan. This research identifies, analyzes, and interprets cultural symbol which sourced from Dayak tribe mantra during Babalai ceremony. The cultural symbols to be identified are the symbols based on Pierce's trilogy of indexes, icons, and symbols. This study aims to describe the Dayak tribe mantra used in Babalai ceremonial and to analyze symbols in the Meratus Dayak’s tribe mantra used during Babalai event in Paramasan, Banjar district of South Kalimantan. Each symbol and icon used in each culture contains its own cultural values that are considered significant in its community. The study of Dayak’s Meratus mantra text would enrich the treasury of language and culture in local-global communities and could strengthen solidarity among nations and countries. The language used as a medium in expressing or expression is a media to know historical evidence as the context of an understanding of the identity of a culture. Cultural identity emerges within a community not only as a color of locality but also as a cultural expression that offers an alternative image in society.